2017
DOI: 10.4103/jpbs.jpbs_86_17
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of oral mucosal lesions among dental patients with mixed habits in Salem district - A study

Abstract: Background:The practice of betel nut chewing with or without tobacco is still practiced in south india, salem inspite of its harmful effects.Methodology:200 Patients visiting the outpatient department, Oral medicine and radiology from Aug 2015 to Aug 2016.Result and Conclusion:In our study, 3 women were exclusively churut smokers. Thirty-eight percent of the dental patients were beedi smoker, 32% were tobacco chewers, 12% were both betel nut and tobacco chewers, 8% were exclusively betel nut chewers, 1% of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 23 publications
0
6
1
Order By: Relevance
“…Majority of patients treated with OSF belonged to group IV-A, which is in sharp contrast to other studies that have reported majority of patients that belonged to Group III-A. [13][14][15] This highlights the increased importance for increased awareness and early referral.…”
Section: Banning Of Areca Nut and Its Products In Pakistancontrasting
confidence: 74%
See 2 more Smart Citations
“…Majority of patients treated with OSF belonged to group IV-A, which is in sharp contrast to other studies that have reported majority of patients that belonged to Group III-A. [13][14][15] This highlights the increased importance for increased awareness and early referral.…”
Section: Banning Of Areca Nut and Its Products In Pakistancontrasting
confidence: 74%
“…Cancer of mouth and throat is the second most common cancer in children and adults of Pakistan as per reports from tertiary care hospitals in Pakistan as there is no official oral cancer registry in Pakistan. 15,26 OSF is a significant health concern particularly in men and women belonging to low socio-economic status and should be regarded as a major public health issue. 6 It is a chronic, progressive disease resulting in loss of fibro elasticity and hardening of the oral mucosa and restriction in opening of the mouth with a significant cancerous potential.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cigarettes were the most popular among smokers (52%), whereas gutkha was the preferred smokeless tobacco product (26.3%). 16 Mehrotra et al and Karthik and Mohan have found betel quid chewing to be more popular among females 13,17 followed by reverse smoking. 18 Our study showed similar results vis-a-vis betel quid chewing, but we did not find any subjects with a reverse smoking habit.…”
Section: Discussionmentioning
confidence: 99%
“…11 Beedi is the most common form of smoking tobacco used among South Asian population among Salem district. 12 Grady et al stated that nicotine in tobacco smoke when inhaled stimulates the nicotinic anticholinergic receptors causing dopamine release from the corpus striatum, pre-frontal cortex, nucleus accumbens regions producing a euphoric effect, thereby causing an addiction. 13 Benowitz et al stated that nicotine activates the alpha 4 beta 2 receptors in the ventral tegmental area causing dopamine release in the shell of nucleus accumbens.…”
Section: Discussionmentioning
confidence: 99%